The Strategic Role of Notaries in Guaranteeing Financial Rights in Mixed Marriages: A Study of Marriage Agreements - Sisca Zulistia; Susi Susantijo (Ipso Jure, 2025)
When a foreign citizen and an Indonesian citizen get married, they participate in a mixed marriage, which is governed by the laws of both countries. The protection of the financial rights of the spouse is one of the many complicated legal issues that arise in mixed marriages between Indonesian citizens and foreigners. The differences in the legal system between the couple's countries of origin are an important background in the need for the preparation of a valid and fair marriage agreement. A marriage agreement is an important instrument to regulate property ownership, financial obligations, and the protection of the rights of each party, both during the marriage and after the divorce. This research formulates two main problems, namely how to regulate the preparation of marriage agreements in mixed marriages, and how the role of notaries in ensuring the protection of the financial rights of mixed couples. The purpose of this study is to analyze the strategic role of notaries in these contexts and assess the effectiveness of the available legal protection mechanisms. This study uses a normative juridical method with a legislative approach and a study of legal documents. The results of the study show that notaries have an important role not only in the preparation of marriage agreement deeds, but also in providing legal education, bridging differences in the legal system, and anticipating potential disputes through the preparation of appropriate dispute resolution clauses. In conclusion, notaries are key actors in ensuring the financial rights of couples in mixed marriages, through agreements that are fair, legal, and in line with the principles of Indonesian and international law